External Debt and Economic Growth: Evident from South Asian Countries - Zuhroh, Idah; Pristiva, Desy (Universitas Negeri Semarang, 2022)
External debt is one of the fiscal policies that are still widely used by developing countries as an instrument of development capital. Limited capital in development in developing countries is one of the obstacles to the accelerated development of a country, one of which is in South Asian countries. This study aims to determine the effects of external debt, exports, foreign direct investment (FDI), and exchange rates on economic growth in South Asian countries using panel data in eight countries with a 2005–2019 series. data in the form of panel data from several data sources, including the World Bank, UnctadSTAT, and the Asian Development Bank. The panel data regression method is used to see the effect of external debt and other macroeconomic variables on economic growth as proxied by GDP growth for South Asian countries. The results of the analysis found that external debt, exports, and FDI had a significant positive effect on economic growth in South Asian countries. However, the exchange rate has a significant negative effect on economic growth in South Asian countries. These results imply that external debt is still needed as a policy instrument in development and economic growth in South Asia, with debt management for the allocation of productive activities. As indicated by increasing welfare and national economic growth, external debt management can accelerate development.